Życie w paschalnym zaufaniu - Bitter, Gottfried (Horyzonty Wychowania, 2017)
Many contemporary societies are experiencing deep culturaltransformations. Until recently, discovering values and preservingthem in social and private life was an integral part of traditionpassed on from generation to generation. Today, this task is left tothe individual. It also refers to the sphere of religion. Nowadays,everybody has to build his own world of religious images. Functioningwell until recently, traditional forms of passing on the faithcollapsed to a large degree. Everybody has to settle in the world ofreligion, in a way, under his own steam, which is the reason formiscellaneous „religiousnesses” and „christianities” emerging. Inthis context, the answer to the question about the specificity ofChristianity, about Christian identity, becomes an inevitable necessity.Explaining the idea of Christianity, its peculiarity, has becomethe necessity for the Christians themselves, for Christian communitiesand churches, but also for non-Christians.The author of this article makes an attempt to show that thequestion about Christian identity is one of the oldest questionsasked by Christian tradition. Already St. Paul provides the modelanswer (1 Cor 15, 3a-5). Also, the twentieth-century theologiansface this question and try to reply to it according to their times(cf. R. Guardini, K. Rahner). In the end, the author himself makesa bold attempt to present his own concise formula of Christianidentity (Life in paschal trust), in order to encourage others toseek their own formulas based on a sound foundation of Judeo-Christian tradition as well as their own Christian traditions. Inthis new way, individual autonomy in the sphere of religiousnessand Christian identity may interweave and complement oneanother in the concrete way of life of each Christian.